Detection and Determination of Critical Phosphorus Source Areas Using Remote Sensing Data in Al-Abrash basin in Syria - Lbraheem, Hani Mohammad; Edriss, Younes; Al-Shater, Mohammad Said (Annals of Arid Zone, 2020)
The critical phosphorus source areas (CPSAs) were determined by identifying and integrating both the transport factors of phosphorus (soil erosion, surface runoff, slope and Euclidean distance from water resources) and source factors (total phosphorus in the soil, land use and land cover) in Al-Abrash basin in Tartu’s province, Syria during the winter season 2017-2018. The input data to the models, which were performed to determine the above mentioned six factors, consists of information through remote sensing, meteorological and soil data. The study indicated that CPSAs were located along Al-Abrash riverbanks. There are large areas of field crops and orchards in these regions, which relatively have high quantities of total phosphorus in the soils due to use of organic and inorganic fertilizers in previous stages and due to proximity of these agricultural areas to water resources (Al–Abrash river). In addition, CPSAs were located in the eastern part of Al-Abrash dam along the village of Beit Al-Sheikh Younis, and these regions are affected by high soil erosion due to various factors. The central and northern part of the study area was outside the water basin along the Smakah, Dananir, Ras Al Deir, Al-Awiya, Mashta Ghanem villages, which were planted by citrus and field crops. The study reflected that remote sensing data were basic for providing input for mathematical models so as to perform spatial analysis of CPSAs. Key word: Phosphorus loss, soil erosion, runoff, land use, Al-Abrash basin.